Differences in HIV natural history among African and non-African seroconverters in Europe and seroconverters in sub-Saharan Africa. - Nikos Pantazis; Charles Morrison; Pauli N Amornkul; Charlotte Lewden; Robert A Salata; Albert Minga; Tsungai Chipato; Harold Jaffe; Shabir Lakhi; Etienne Karita; Kholoud Porter; Laurence Meyer; et al. (PLoS ONE)
Introduction It is unknown whether HIV treatment guidelines, based on resource-rich country cohorts, are applicable to African populations. Methods We estimated CD4 cell loss in ART-naïve, AIDS-free individuals using mixed models allowing for random intercept and slope, and time from seroconversion to clinical AIDS, death and antiretroviral therapy (ART) initiation by survival methods. Using CASCADE data from 20 European and 3 sub-Saharan African (SSA) cohorts of heterosexually-infected individuals, aged ≥15 years, infected ≥2000, we compared estimates between non-African Europeans, Africans in Europe, and Africans in SSA. Results Of 1,959 (913 non-Africans, 302 Europeans-African origin, 744 SSA), two-thirds were female; median age at seroconversion was 31 years. Individuals in SSA progressed faster to clinical AIDS but not to death or non-TB AIDS. They also initiated ART later than Europeans and at lower CD4 cell counts. In adjusted models, Africans (especially from Europe) had lower CD4 counts at seroconversion and slower CD4 decline than non-African Europeans. Median (95% CI) CD4 count at seroconversion for a 15-29 year old woman was 607 (588-627) (non-African European), 469 (442-497) (European-African origin) and 570 (551-589) (SSA) cells/µL with respective CD4 decline during the first 4 years of 259 (228-289), 155 (110-200), and 199 (174-224) cells/µL (p<0.01). Discussion Despite differences in CD4 cell count evolution, death and non-TB AIDS rates were similar across study groups. It is therefore prudent to apply current ART guidelines from resource-rich countries to African populations.